Uruguay : Trade Competitiveness Diagnostic - Portugal, Alberto; Reyes, Jose-Daniel; Varela, Gonzalo (World Bank, Washington, DC, 2015)
As a small economy, Uruguay’s growth and poverty reduction prospects are closely related to its performance in international markets. This report analyzes export dynamics in Uruguay over the period 2000-2013, benchmarking them against relevant comparator countries. It looks at export outcomes through four different dimensions of export performance: (1) the evolution, composition, and growth orientation of the country’s export basket; (2) the degree of diversification across products and markets; (3) the level of sophistication and quality; and (4) the survival rate of export relationships. The report offers a number of hypotheses for an in-depth competitiveness diagnostic of Uruguay’s external sector, as well as policy recommendations to increase integration and to gain from it. In addition to the real depreciation of the peso that followed the crisis, the international prices of Uruguay’s main export products soared. This stimulated investment in technological improvements in the production of these natural-resource-intensive products. Section one analyzes the macroeconomic environment in which exporters operate in Uruguay during the period of analysis. Section two looks at level, growth, composition, and market share performance of Uruguay’s exports, as well as the country’s main trading destinations. Section three focuses on the diversification of products and markets, considering several measures of concentration, including the share of top five products and markets in exports, and the Hirschman-Herfindahl index for Uruguay’s export portfolio. Sections four and five address quality and sophistication and survival, respectively.